Efek Marinasi pada Berbagai Sari Buah Terhadap Nilai Susut Masak dan pH Daging Ayam Petelur Afkir: The Effect of Marinating in Various Fruit Juices on Cooking Losses and pH Value of Culled Laying Hens Meat - Ismiarti; Luthfi, Nadlirotun; Suryani, Hasna Fajar (Fakultas Peternakan Universitas Jambi, 2023)
Pineapple, kiwi, and papaya fruits contain enzyme that were classified as proteolytic enzymes which affected to the characteristic of culled laying hens. This study aimed to investigate cooking losses and pH of culled laying hens marinated using pineapple, kiwi, and papaya juice. The breast of culled laying hens 94 weeks, pinnepale, kiwi, and papaya juice were used in this research. The study was conducted experimentally using a one-way completely randomized design (CRD) consisting of 4 treatments and 5 replications. The treatments consisted of P0 (marinated with 10% distilled water), P1 (marinated with 10% pineapple juice), P2 (marinated with 10% kiwi fruit juice), and P3 (marinated with 10% papaya juice). The data obtained were analyzed by analysis of variance (Anova) and the treatment with a significant effect was followed by the Duncan's Multiple Range Test (DMRT).Â The results showed that marinating meat of culled laying in pineapple, kiwi, or papaya juice had a very significant effect (p<0.01) on cooking loss and pH value. Marinating in papaya juice resulted in the highest cooking loss in meat of culled layers, while marinating in kiwi fruit juice lowered the pH value. In conclusion, marination in pineapple, kiwi, and papaya juice is effective for improving cooking losses and the pH of meat of culled laying hens.